IGR J16318-4848: optical and near-infrared spectroscopy of the most absorbed B[e] supergiant X-ray binary with VLT/X-Shooter. Issue Volume 14:Issue S346(2019) (August 2018) - Fortin, F.; Chaty, S.; Goldoni, P.; Goldwurm, A.
Abstract: The supergiant high-mass X-ray binary IGR J16318-4848 was detected by INTEGRAL in 2003 and distinguishes itself by its high intrinsic absorption and B[e] phenomenon. It is the perfect candidate to study both binary interaction and the environment of supergiant B[e] stars. We report on VLT/X-Shooter observations from July 2012 in both optical and near-infrared, which provide unprecedented wide-range, well-resolved spectra of IGR J16318-4848 from 0.5 to 2.5 μ m. Adding VLT/VISIR and Herschel data, the spectral energy distribution fitting allows us to further constrain the contribution of each emission region (central star, irradiated rim, dusty disc). We derive geometrical parameters using the numerous emitting and absorbing elements in each different sites in the binary. Various line shapes are detected, such as P-Cygni profiles and flat-topped lines, which are the signature of outflowing material. Preliminary results confirm the edge-on line of sight and the equatorial configuration of expanding material, along with the detection of a potentially very collimated polar outflow. These are evidence that the extreme environment of IGR J16318-4848 is ideal to have a better grasp of highly obscured high-mass X-ray binaries.